The Study of Translation and Structural equivalent of absolute ablative with a focus on the translation of Fooladvand (the Case study of Surah Al-Nisa) - Hossein Khani Kalgay; Kosar Halalkhore (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2015)
One of the essential principles of faithful and the favorable translations is establishment of the balance in thestructures of thesource and target language.Linguistic structures, especiallysyntax structure have basic role in the process of translation and linguistic analysis. Absolute ablative is a syntax role that it has not structural similarityin Persianand its equivalent should be foundbase onits structuralequivalentin Persiannamelyadverb and itsdifferent typestothemessage ofthe BibleQuranbeavailablefor the thirst of divineknowledge Closer and moreaccurate.Carelessnesstothisissue makes that translation of absolute ablative be position of slipping in Persian translations of the Holy Quran. Accordingly, we examined Fooladvand's translation and theresults show that the recenttranslationhas been successfulto find theequivalent for a variety of absoluteablativemorethancontemporarytranslationsSo that ithas been the greatestsuccessin finding of thestructuralequivalents for injunctive absolute ablative and all the injunctive absolute ablative in Surah Al-Nisaproperlytranslated based on structuralequivalent.